Relationship between Birth Interval and Maternal Education with Supplementary Feeding Practices for Stunting Toddler - Mahisa, Yustira Hanin; Rohmawati, Ninna; Antika, Ruli Bahyu (Department of Nutrition, Faculty of Health Sciences, Universitas Brawijaya Malang, 2024)
Stunting is a significant health problem that can affect the growth and development of toddlers. It is measured according to WHO standards using the height-per-age index, with a score below -2 SD indicating stunting. Supplementary feeding is one of the factors influencing stunting in toddlers, and it can be influenced by birth interval and mother’s education level, which in turn influence changes in the child’s nutritional status. This study aimed to analyze the relationship between birth interval and maternal education level with the rate of supplementary feeding in stunted toddlers aged 24-59 months in Cumedak Village, Jember Regency. An observational analytic method with a cross-sectional study design was used, involving 54 respondents of stunting toddlers aged 24-59 months. Data were collected through interviews and a 2x24-hour food recall method. The results show that the supplementary feeding practices were categorized as less (53.7%). A Chi-square statistical test revealed no significant relationship between birth interval and supplementary feeding rate (p = 0.715, p > 0.05), but there was a significant relationship between the mother’s education level and supplementary feeding rate (p = 0.002, p < 0.05). In conclusion, there is no relationship between birth interval and the quality of supplementary feeding, but there is a significant relationship between maternal education level and the quality of supplementary feeding.